2017
DOI: 10.1016/j.jcorpfin.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Stock market listing and the use of trade credit: Evidence from public and private firms

Abstract: This paper examines differences in the use of trade credit by publicly listed firms and their privately held counterparts. We show that public firms maintain a significantly lower level of trade credit than private firms. This finding is consistent with the argument that public firms rely less on supplier financing because of their greater access to cheaper and less risky sources of external capital. We further find that while public and private firms actively seek to adjust toward their optimal trade credit l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 90 publications
(128 reference statements)
11
83
0
Order By: Relevance
“…Breza and Liberman (2017), on the other hand, provide evidence that similar restrictions on the maturity of trade credit -such as that which a large buyer in Chile could obtain from small suppliers -lead to a reduction in trade with small firms. Abdulla et al (2017) find that privately held firms rely more on trade credit than do publicly listed companies.…”
Section: Introductionmentioning
confidence: 89%
“…Breza and Liberman (2017), on the other hand, provide evidence that similar restrictions on the maturity of trade credit -such as that which a large buyer in Chile could obtain from small suppliers -lead to a reduction in trade with small firms. Abdulla et al (2017) find that privately held firms rely more on trade credit than do publicly listed companies.…”
Section: Introductionmentioning
confidence: 89%
“…Thus, firms can use trade payables to optimise inventory levels. Suppliers' credit is the main source of inventory financing (Demirgüç-Kunt and Maksimovic 1999) because it is easier to arrange than a bank loan (Abdulla et al 2017). In fact, over 80% of merchandise in the UK is financed by suppliers' credit (Peel et al 2000).…”
Section: Abnormal Inventory and Trade Payablesmentioning
confidence: 99%
“…The research of J. Murfin, Njoroge [10] proved that investment-grade buyers will obtain loans from smaller suppliers and force suppliers to reduce investment, which is more obvious during the credit crunch period; Jean. NoelBarrot [11] found out that providing restrictions on trade credit can greatly reduce the risk of corporate reporting violations by studied reforms in the French transportation industry; Based on the research on equity capital market and trade credit financing conducted by Yomna Abdulla et al [12], the scholar Chenguang Shang [13] demonstrated that companies with high stock liquidity rely less on commercial credit financing by measuring stock liquidity and trade credit measures, this relationship is more significant for companies that are constrained by financing and rely on short-term debt.…”
Section: The Complementary Relationship Between Commercial Credit and Bank Creditmentioning
confidence: 99%